Maltol, a naturally occurring flavor enhancer, ameliorates cisplatin-induced apoptosis by inhibiting NLRP3 inflammasome activation by modulating ROS-mediated oxidative stress. (July 2022) - Wang, Wen-ting; Fan, Mei-ling; Hu, Jun-nan; Sha, Ji-yue; Zhang, Hao; Wang, Zi; Zhang, Jun-jie; Wang, Shi-Han; Zheng, Si-wen; Li, Wei
Graphical abstract: Highlights: This article is the first to describe the protective effect of maltol on cisplatin-induced intestinal injury in vitro and in vivo . This study clarifies that cisplatin stimulates the body to release excessive ROS to induce oxidative stress, which in turn triggers the activation of the inflammasome NLRP3, resulting in the occurrence of pyroptosis. This study is the first to explore the protective effect of maltol on intestinal tract from the mechanism of oxidative stress, pyroptosis and apoptosis. Abstract: Although the antagonistic effects of saponins (Ginsenosides) from ginseng on the side effects caused by cisplatin have been widely confirmed, there are few reports on the non-saponins of small molecules. Maltol, as an important active ingredient and a naturally occurring flavor enhancer produced in the process of red ginseng, has been proven to have good pharmacological activity. The purpose of this study is to explore the protective effect and possible mechanisms of maltol on cisplatin-induced intestinal toxicity in vivo and in vitro . A single injection of cisplatin (20 mg/kg) caused significant damage to the intestinal function of mice, shrinkage of the small intestine, and sharply increased the diamine oxidase (DAO) index of intestinal function, which exacerbates the occurrence of oxidative stress damage. After administration of maltol (50 and 100 mg/kg), these symptoms were remarkably relieved. Notably, in cultured IEC-6 cells, maltol treatment improved the occurrence of oxidative stress during cisplatin exposure, significantly inhibited the excessive release of ROS, and attenuated the cisplatin-induced increase in NLRP3 inflammasome release. The findings indicating that maltol inhibits oxidative stress and pyroptosis, and further reduces cisplatin-induced apoptosis. In conclusion, the results of this study indicated that maltol exerts the protective effects of cisplatin-induced intestinal toxicity by reducing the release of ROS and inhibiting the activation of apoptosis.